Research Performance of ICAR-Central Institute of Fisheries Education, India: A Scientometric Study - S. Abuthagir Iburahim; R. Bharathi Rathinam; Vidhya. V (Journal of Indian Fisheries Association, 2023)
A scientometric analysis on publication outputs of ICAR-Central Institute of Fisheries Education (CIFE) was conducted in the Web of Science (WoS) platform from 1998-2020. A total of 1092 research publications were examined using bibliometric indicators such as h-index, ACPP and WoS citations to understand the changes in various facets of the scientific outputs of ICAR-CIFE including its growth, authorship collaboration, publication pattern, international collaboration. Increasing trend was observed in the year wise publications from ICAR-CIFE from 1988-2020. The maximum ACCP was recorded in the year 2006 with 38.57 citations. The network visualisation of authors collaboration exhibited several discipline wise clusters compared to inter discipline collaboration. The highly cited publication from ICAR-CIFE during 1988-2020 was published in the journal of Fish Physiology and Biochemistry with the impact factor of 1.79 for 2020. Indian Journal of Fisheries, Fishery Technology and Indian Journal of Geo Marine Science were identified as top three journals where the maximum number of publications from ICAR-CIFE published. This study represented a snapshot of the scientific literature published in journals indexed in the Scopus database from ICAR-CIFE. The number of publication from Web of science database is far low compared to the annual reports of the institution in the resepective years.